Effect of land-use change on traffic peak hour factor - Phahlane, Motsepe Herbert (Vaal University of Technology, 2012)
Growth in land development in South Africa resulted in large increase in traffic volumes. A Traffic Impact Assessment (TIA), as a traffic engineering tool, is commonly used to assess the possible effects of a land development project on the transportation and traffic system. During the TIA process, capacity analysis is performed to indicate the measures of effectiveness of the intersection. Intersection capacity analysis in South Africa by engineers is done on the basis of default values of the Peak Hour Factor (PHF) provided by the Highway Capacity Manual (HCM) or limited traffic counts. However, the default value of PHF may be significantly affected by new developments in the neighbourhood of the intersection. This study aimed at investigating the impact land-use change has on the existing intersection PHF, thus predicting values per land-use type. Intersections with traffic counts conducted before and after land-use change in vicinity were selected and investigated. The results showed that change in land-use has an impact on the existing PHF. They also assist in identifying the appropriate intersections to predict the PHF per land-use type. Intersections were identified and analysed, and this led to the development of a design chart showing the predicted PHF per land-use type selected and measures to consider during traffic analysis. Intersection capacity analysis was performed to compare the results using the predicted PHF and the HCM default values. The results showed that traffic flow rate was adjusted by up to 26% when using the default values, 0.92 and 0.95. The results also showed that the default values could overestimate the volume to capacity ratio and the average delay by up to 15% and 35%, respectively. It was then concluded that the use of HCM default values of the PHF for every land-use type will have an effect of the final roadway design results. The computed PHF values for each land-use type were then recommended to be used to ensure fairness and consistency in traffic analysis.
M. Tech. (Department of Civil Engineering and Building, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Transportation; Land-use; Traffic impact; Land use -- South Africa.; Transportation.; Dissertations, Academic -- South Africa.